Economic Growth in Croatia : Potential and Constraints - Moore, David (IMF Working Papers; Working Paper, 2007)
This paper examines the factors and constraints that affect recent and potential growth in Croatia, as well as policies that can influence it. On current productivity trends, it estimates Croatia's potential growth rate at 4-4 1\2 percent, a result reasonably robust to different methodologies. To sustain growth at a higher rate in line with the authorities' aspirations, the analysis highlights the critical need to improve the business environment through further measures to reduce the administrative burden, legal uncertainties, and corruption. It also emphasizes the importance of attracting more greenfield foreign direct investment, and reforms to reduce the role of the state in the economy through fiscal consolidation and faster privatization.